2018
DOI: 10.3390/met8030169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Steel Subjected to the Thermomechanical Control Process with Respect to Weldability

Abstract: Abstract:The study is concerned with the assessment of the weldability of steel S700MC subjected to the thermomechanical control process (TMCP) and precipitation hardening and characterised by a high yield point. Appropriate mechanical and plastic properties of steel S700MC were obtained using the thermomechanical control process through precipitation, solution, and strain hardening as well as by using grain-refinement-related processes. Constituents responsible for the hardening of steel S700MC include Ti, Nb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 36 publications
3
31
0
Order By: Relevance
“…The thermomechanically controlled welding process for HSS S700MC requires the consideration of several factors, such as mechanical properties, chemical composition, welding process, and choice of filler wire [10][11][12][13][14][15]. Guo et al [16] used autogenous laser welding (ALW) and multi-pass ultra-narrow gap laser welding (NGLW) in the evaluation of the mechanical properties and microstructure of a welded joint of S700MC and S960QC HSS.…”
Section: Introductionmentioning
confidence: 99%
“…The thermomechanically controlled welding process for HSS S700MC requires the consideration of several factors, such as mechanical properties, chemical composition, welding process, and choice of filler wire [10][11][12][13][14][15]. Guo et al [16] used autogenous laser welding (ALW) and multi-pass ultra-narrow gap laser welding (NGLW) in the evaluation of the mechanical properties and microstructure of a welded joint of S700MC and S960QC HSS.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of reference publications [1,5,7,10,18,22] and individual research [4,9,17,38] revealed that, in cases of S700MC steel, the analysis of the phase transformations of austenite was affected by welding thermal cycles and the value of carbon equivalent cannot constitute the only factors taken into consideration during the assessment of weldability. The tested steel has a low carbon content (0.056% by mass), limited primarily by hardening elements (titanium and niobium), which reduces its role in hardening by supersaturation of ferrite and by limiting its action during γ-α transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Before welding, the edges of the plates were dried by being heated at a temperature of 65 °C . The results of strength tests and changes in structure were referred to the joints made using the MAG method [38]. Additional material used solid wire G Mn4Ni1.5CrMo.…”
Section: Welding Processmentioning
confidence: 99%
See 2 more Smart Citations